The quality maturity model: assessing organizational quality culture in palm oil organization (upstream) / Hasmah Che Mat and Muhamad Zahid Muhamad - Che Mat, Hasmah; Muhamad, Muhamad Zahid (Faculty of Plantation and Agrotechnology, 2018)
Malaysia palm oil is the biggest profits producing contributor for our economy. Quality management practices still lacking of maturity model that are needed in palm oil organization. The purpose of this research is to facilitate the participation of palm oil directors with quality culture issues. This is achieved through a new interpretation of the quality culture concept, the Quality Maturity Model. The QMM enables palm oil directors to assess their location in a way of quality culture, leading them to the next step forward, which allows them to progress over time, and enable them to compare themselves to others and learn from good practice. This research presents a systematic literature review (SLR) on assessment of quality management maturity practices in palm oil organization and also relates to the Design Science Research Methodology as a framework and used Grounded theory methods to create the Quality Maturity Model. The QMM defines 30 elements of quality culture, which are grouped into eight elements: Management of the organisation: environmental sensing: learning organisation attributes: attitude to change: attitude to quality: leadership; investment in staff; and alignment. The QMM has five maturity levels describing the progress from low quality maturity to high quality maturity for each of the elements.